Grammar Instruction in Communicative Language Teaching Classrooms: Student Teachers’ Perceptions - Muhamad Holandyah; Dian Erlina; Lenny Marzulina; Fitria Rembulan Ramadhani (Edukasi, 2021)
The aim of this study was to find out the teachers and students’ perception toward grammar instruction in communicative language teaching classrooms. The participants of this study were two teachers and four students from an Islamic junior high school (Madrasah). We used a case study method to conduct this research to identify teachers and students’ perception in teaching and learning grammar instruction in communicative language teaching classroom. The data were collected by using interviews. The data were analyzed by using thematic analysis. The findings indicated that there were five indicators on student teacher’s perception; 1) grammar was a crucial component in improving English skills; 2) using classroom activities to promote communicative activities in the classroom; 3) error correction was seen as one of processes to create students in mastering materials; 4) teaching grammar instruction in CLT classroom, teachers act as motivator and facilitate all students’ need; 5) students should take part on the process of learning.